Nephrocalcinosis tendency does not worsen under burosumab treatment for X-linked hypophosphatemic rickets: a multicenter pediatric study - Levi, Shelly; Landau, Daniel; Davidovits, Miriam; Shapira Rootman, Mika; Brener, Avivit; Gal, Shoshana; Borovitz, Yael; Goldberg, Ori; Bello, Rachel; Cleper, Roxana; Lebenthal, Yael; Levy-Shraga, Yael; et al. (Frontiers in Pediatrics, 2024)
Background: X-linked hypophosphatemic rickets (XLH) is associated with uninhibited FGF23 activity, which leads to phosphaturia, hypophosphatemia and depressed active vitamin D (1,25OH2D) levels. Conventional treatment with phosphate supplements and vitamin D analogs may lead to hypercalciuria (HC), nephrocalcinosis (NC) and hyperparathyroidism. We investigated the effects of burosumab treatment, an anti-FGF23 monoclonal antibody recently approved for XLH, on these complications.Methods: This retrospective study included children with XLH who were treated with burosumab for at least one year at one of three referral centers. Clinical and biochemical potential treatment outcomes were regularly followed, including multiple urine calcium measurements and NC severity score (0= no NC, 3= worse NC).Results: Twenty-six (13 male) children aged 7.6±3.9 years were followed for 27.5±9.6 months. Mean serum phosphate levels rapidly increased from 2.67±0.61 at baseline to 3.57±0.53 mg/dL after 3 months (p< 0.001) and remained stable thereafter. Concomitant decreases were observed in phosphaturia, serum alkaline phosphatase and parathyroid hormone. HC (U-Ca/Cr > 0.2 mg/mg) was detected in 2/26 (7.7%) patients before burosumab initiation, resolved in one and persisted, albeit improved, in the second. Two patients were newly diagnosed with HC, 15 and 3 months after therapy, which persisted in one of them despite dose reduction attempts. Seven patients had NC at baseline (mean score: 1.8±0.34), but none showed deterioration or developed new NC.In children with XLH treated with burosumab, HC was a rare side effect and preexisting NC did not worsen.